Eco Lindi Without Odors for Organic Waste Management, Training in Various Organic Waste Crafts, and Digital Marketing for Improving the Family Economy - Pikanthi Diwanti, Dyah; Susilawati, Desi; Safitri, Mutiara Dien; Arya, Bramadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Thai government has realized the serious problem of environmental pollution due to plastic waste. In everyday life, plastic has become an important and integral part of societies around the world due to its various uses, such as packaging, agriculture, auto parts, electronic applications and medical devices. This results in approximately 2 million tons of plastic waste being generated per year. Managing organic waste in the form of stacked buckets does not require large areas of land and equipment is easy to obtain. This activity includes: a. training and practice in making stacked buckets, b. training in making crafts from inorganic waste, and c. digital marketing training for product sales. The expected output of this activity is that Muhammadiyah residents in Thailand have an understanding regarding making stacking buckets independently so that organic waste management is more optimal. The next output is increasing the community's skills in making crafts by utilizing inorganic waste and turning it into a product to be marketed and can increase family income and well-being.